La manucure et la pédicure dans la ville de Ouagadougou (Burkina Faso): pratiques et risqué - Korsaga-Somé, Nina (Pan Afr Med J, 2016)
Pedicure-manicure represents the aesthetic care of hands, feet and nails. In Burkina Faso, the use of manicure-pedicure products, the techniques used and the level of risk remain unknown. The aim of our study was to evaluate the practice of manicure-pedicure in the city of Ouagadougou. We conducted a descriptive cross-sectional study of all practitioners with at least six months experience in aesthetic care and customers present at the time of the survey from December 2010 to November 2012. We interviewed a total of 313 practitioners and 313 clients. The average age of practitioners was 19 years and of customers was 32.2 years. Fixed location practitioners were mostly women (96.87%) while mobile practitioners were mostly men (68.37%); 64.53% of customers were women. The percentage of practitioners who did not receive professional training was 93.92%. 29.7% of practitioners soaked the instruments in javel water for at least ten minutes; 75.71% knew that the use of certain tools was dangerous and 26.51% had side effects. 40.25% of customers knew that the used equipment may pose some risks and 30.35% were victims of accidents. The manicure and pedicure is done in hair salons by untrained hairdressers to the professional practice. The origin and composition of the products is not known. Not recommended products are used (foot soak shampoo, razor blade and scissors for feet scraping). The use of manicure and/or pedicure is sometimes necessary but that should not obscure the risks to which it exposes customers. Customers education and practitioners training seem necessary to minimize risks.